Effect of Immediate Initiation of Antiretroviral Treatment in HIV-Positive Individuals Aged 50 Years or Older. (1st November 2017) - Lodi, Sara; Costagliola, Dominique; Sabin, Caroline; del Amo, Julia; Logan, Roger; Abgrall, Sophie; Reiss, Peter; van Sighem, Ard; Jose, Sophie; Blanco, Jose-Ramon; Hernando, Victoria; Bucher, Heiner C.; et al.
Abstract : Background: Clinical guidelines recommend immediate initiation of combined antiretroviral therapy for all HIV-positive individuals. However, those guidelines are based on trials of relatively young participants. Methods: We included HIV-positive antiretroviral therapy–naive, AIDS-free individuals aged 50–70 years after 2004 in the HIV-CAUSAL Collaboration. We used the parametric g-formula to estimate the 5-year risk of all-cause and non-AIDS mortality under (1) immediate initiation at baseline and initiation at CD4 count, (2) <500 cells/mm 3, and (3) <350 cells/mm 3 . Results were presented separately for the general HIV population and for a US Veterans cohort with high mortality. Results: The study included 9596 individuals (28% US Veterans) with median (interquantile range) age of 55 (52–60) years and CD4 count of 336 (182–513) at baseline. The 5-year risk of all-cause mortality was 0.40% (95% confidence interval (CI): 0.10 to 0.71) lower for the general HIV population and 1.61% (95% CI: 0.79 to 2.67) lower for US Veterans when comparing immediate initiation vs initiation at CD4 <350 cells/mm 3 . The 5-year risk of non-AIDS mortality was 0.17% (95% CI: −0.07 to 0.43) lower for the general HIV population and 1% (95% CI: 0.31 to 2.00) lower for US Veterans when comparing immediate initiation vs initiation at CD4 <350 cells/mm 3 . Conclusions: Immediate initiation seems to reduce all-cause and non-AIDS mortality in patients aged 50–70 years. Abstract : Supplemental Digital Content is Available in the Text.